Self-purification transformer oil and preparation method thereof
By using modified nanocomposite particles and rare earth doped nanoparticles in transformer oil, the problem of insufficient insulation and breakdown performance of existing transformer oil under high pressure conditions is solved, and the self-purification and performance improvement of oil is achieved.
Patent Information
- Application Number
- CN202411580625.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-14
AI Technical Summary
Existing transformer oils are difficult to meet the requirements of insulation performance and breakdown performance under high pressure conditions, and the stability and function of nanofluids are single.
Using nanocomposite particles and rare earth doped nanoparticles, a self-purified transformer oil is prepared through modification and surface modification. The preparation method of the oil includes mixing vegetable oil, mineral insulating oil, toluene diphenyl phosphate, stearic acid, nanocomposite particles and rare earth doped nanoparticles in a specific proportion, and preparing it through ultrasonic oscillation treatment and filtration.
The transformer oil significantly improves the insulation performance and positive impact breakdown performance under high pressure conditions, and through the self-purification effect of nanocomposite particles, the service life of the oil is extended and the working temperature of the transformer is reduced.
Smart Images

Figure BDA0005122997100000101 
Figure BDA0005122997100000111
Abstract
Description
Technical Field
[0001] The invention relates to self-purifying transformer oil and a preparation method thereof, belonging to the technical field of transformer oil preparation. Background Art
[0002] At present, transformer oil is widely used in today's power industry transformers as a good insulating and heat dissipation medium. In recent years, with the continuous development of ultra-high and ultra-high voltage transmission networks, the design requirements of transformers are developing towards large capacity, miniaturization and high insulation, which puts higher requirements on the strength of insulation in transformers. The statistical results of transformer accidents show that insulation failures caused by impulse overvoltage account for 11% of the total transformer failures. With the increase of ultra-high voltage AC and DC transmission voltage and the large-scale grid connection of intermittent renewable energy, the insulation performance of transformer oil will face more stringent challenges. Improving the breakdown performance of transformer oil is of great significance to ensure the stable operation of ultra-high voltage transformers. Therefore, the insulation performance and positive impulse breakdown performance of transformer oil are crucial. Nanofluids are widely used in industry, chemistry, energy and other fields as a new type of material. Nanoparticles can not only improve the thermal conductivity of its materials, but also effectively improve its electrical properties and anti-aging properties for dielectrics. Nanoparticles are particles with a particle size of 1-100nm. When they are evenly distributed in transformer oil, their particle size is several orders of magnitude smaller than that of common microparticles. Due to their large specific surface area, they are easily agglomerated in liquid dielectrics, thus affecting the stability of nanofluids. Moreover, most of the nanoparticles used in the current research on modified transformer oil are single oxide particles with single functions.
[0003] In view of the above-mentioned defects, the designers have actively carried out research and innovation in order to create a self-purifying transformer oil and a preparation method thereof, so as to make it more valuable for industrial use. Summary of the invention
[0004] In order to solve the above technical problems, the object of the present invention is to provide a self-purifying transformer oil and a preparation method thereof.
[0005] The self-purifying transformer oil of the present invention comprises the following raw materials by weight:
[0006] 20-30 parts vegetable oil;
[0007] 50-60 parts of mineral insulating oil;
[0008] 3-8 parts of toluene diphenyl phosphate;
[0009] 1-2 parts of stearic acid;
[0010] 5-10 parts of nanocomposite particles;
[0011] 0.5-0.7 parts of 2-methyl-benzotriazole;
[0012] The raw materials for preparing the nano composite particles include microcrystalline cellulose, ethanol, sodium hydroxide, ethyl orthosilicate and vinyl triethoxysilane.
[0013] Furthermore, the nanocomposite particles are modified to become rare earth-doped nanoparticles;
[0014] The modified raw materials of the rare earth doped nanoparticles include nano composite particles, polyvinyl pyrrolidone, cerium nitrate and ethanol.
[0015] Furthermore, the rare earth doped nanoparticles are also surface modified to become surface modified nanoparticles;
[0016] The modification raw materials of the surface-modified nanoparticles include rare earth nanoparticles, acetic acid and ethanol.
[0017] Further, the specific preparation steps are:
[0018] (1) By weight, 20 to 30 parts of vegetable oil, 50 to 60 parts of mineral insulating oil, 3 to 8 parts of toluene diphenyl phosphate, 1 to 2 parts of stearic acid, 5 to 10 parts of surface-modified nanoparticles, and 0.5 to 0.7 parts of 2-methyl-benzotriazole are weighed;
[0019] (2) first vacuum filter the vegetable oil at room temperature, then heat it to 80-90° C., then add mineral insulating oil, stir and mix at a speed of 80-100 r / min for 20-30 min, then add toluene diphenyl phosphate, stearic acid, and surface-modified nanoparticles, and treat with ultrasonic oscillation at a power of 800-1000 W for 10-15 min;
[0020] (3) Finally, 2-methyl-benzotriazole is added and the ultrasonic oscillation treatment is continued for 10-15 minutes to obtain self-purifying transformer oil.
[0021] Furthermore, the preparation method of the surface modified nanoparticles is:
[0022] Rare earth nanoparticles, acetic acid and ethanol are mixed in a mass ratio of 1:24:250 and put into an ultrasonic disperser for uniform dispersion. The dispersion is then refluxed at 70-75°C for 2-3 hours. After cooling to room temperature, the precipitate is separated, washed three times with ethanol, and then dried at 70°C for 2-3 hours to obtain surface-modified nanoparticles.
[0023] Furthermore, the preparation method of the rare earth nanoparticles is:
[0024] (1) mixing and dispersing the nanocomposite particles and a 30% by mass polyvinyl pyrrolidone ethanol solution at a mass ratio of 1:100, transferring the mixture into a three-necked flask, stirring the mixture at a speed of 300 r / min, and adding cerium nitrate in an amount of 20 to 25% by mass of the nanocomposite particles into the three-necked flask during the stirring process;
[0025] (2) After the addition of cerium nitrate is completed, the temperature is continued to rise to 80-85° C. to react until the ethanol is completely evaporated, and the remaining product is placed in an oven and dried at 200° C. for 3-5 hours. The product is then wet-milled in a ball mill for 12 hours and passed through a 200-mesh sieve to obtain rare earth-doped nanoparticles.
[0026] Furthermore, the preparation method of the nanocomposite particles is:
[0027] (1) A microcrystalline cellulose ethanol dispersion with a mass concentration of 0.2 g / mL and a sodium hydroxide solution with a mass fraction of 8% are mixed in a volume ratio of 1:2, and the mixture is swollen at room temperature for 3 to 4 hours and then vacuum filtered to obtain a solid powder. The obtained solid powder is dispersed in ethanol and stirred to be uniformly dispersed to obtain a dispersion with a mass fraction of 10%;
[0028] (2) Ethyl orthosilicate, vinyl triethoxysilane and ethanol are mixed in a mass ratio of 3:1:100 and loaded into a three-necked flask. The dispersion is then added dropwise into the three-necked flask using a separatory funnel at a water bath temperature of 60 to 65°C. The dropping time is controlled to be 5 to 10 min. After stirring for 50 to 60 min, the mixture is allowed to stand for 30 to 40 min, and a solid filtrate is obtained by vacuum filtration. The solid filtrate is vacuum dried in a vacuum drying oven at 80°C for 6 to 8 h to obtain nanocomposite particles.
[0029] By means of the above scheme, the present invention has at least the following advantages:
[0030] (1) The present invention uses sodium hydroxide solution to swell the cellulose material to form a reaction layer on the cellulose surface, and then heats and dries the reaction layer to form gaps to form a reaction space, so that nano-SiO2 particles formed by hydrolysis of tetraethyl orthosilicate are combined with the cellulose material, and the steric hindrance of nano-cellulose prevents the aggregation and precipitation of nano-particles, thereby improving its synergistic effect. The present invention utilizes the fact that there are a large number of hydroxyl groups on cellulose molecules. Each repeating unit contains 1 primary hydroxyl group and 2 secondary hydroxyl groups, but intramolecular hydrogen bonds and intermolecular hydrogen bonds are easily formed between hydroxyl groups, which limits the adsorption. Therefore, the present invention introduces nanofluids to open the bonds between hydroxyl groups, thereby improving the adsorption activity of cellulose molecules, and adding them to the transformer After being immersed in oil, the modified cellulose material has good adsorption performance. A large number of polar groups exist on the molecule, which makes the molecule have extremely strong oleophobicity. Therefore, this feature can be used to adsorb free micro-water and impurities in the transformer oil. The AC breakdown voltage is obviously affected by the free micro-water content. When the free micro-water content is high, the breakdown voltage value is relatively low. The addition of the composite nanoparticles of the present invention can adsorb and aggregate harmful inclusions and free micro-water in the transformer oil, further improving the insulation performance and positive impact breakdown performance of the modified transformer oil. After using for a period of time, the nano composite particles that adsorb and aggregate inclusions and micro-water are filtered and removed, and new nano composite particles are added again to achieve the self-purification effect of the transformer oil.
[0031] (2) The rare earth element doped in the rare earth-doped nanoparticles of the present invention is easy to react with harmful impurities such as sulfur and oxygen in transformer oil to generate high melting point compounds, which can be adsorbed and gathered by its own cellulose component and discharged later, thereby reducing harmful inclusions in the oil and further improving the insulation performance of the modified transformer oil. The rare earth composite particles themselves have a high thermal conductivity. When they are evenly dispersed in the transformer oil, they can serve as a channel for heat conduction, improve the thermal conductivity of the transformer oil, and then improve its thermal conductivity.
[0032] In addition, the active groups or electrical properties on the surface of rare earth composite particles can be compounded with molecules in transformer oil by physical or chemical methods, thereby enhancing the interfacial compatibility between particles and oil molecules. This enhanced compatibility helps to reduce the agglomeration and precipitation of particles in oil, maintain their uniform dispersion in oil, and thus improve the insulation performance of modified transformer oil.
[0033] (3) The present invention is adsorbed on the nanoparticle surface by acetic acid in a bidentate chelating coordination mode, and the surface-modified nanoparticles greatly change the development form of the streamer in the transformer oil, suppress the development speed of the streamer, and improve the positive impact breakdown performance of the transformer oil. The carbon chain structure of acetic acid is shorter than other carboxylic acids, so after the nanoparticles modified by it are added to the transformer oil, more shallow traps are introduced, which will increase the migration rate of the electrons in the nano oil, prompt the electrons generated by field ionization to leave the positive ions quickly, so that the electric field of the charge generated in the low-density area of the nano oil is increased compared with pure oil, thereby weakening the electric field in the low-density area. Like this, the field intensity of the streamer head in the nano oil will be reduced, preventing the formation of new discharge paths, and then weakening the development speed of the streamer, so the acetic acid modified nanoparticles have the best effect on the impact breakdown performance of the transformer oil.
[0034] The good interfacial compatibility between the rare earth composite particles and transformer oil helps reduce interfacial thermal resistance, allowing heat to be transferred more smoothly in the oil. This helps improve the heat dissipation efficiency of the transformer, reduce its operating temperature, and thus extend its service life.
[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0036] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0037] (1) A microcrystalline cellulose ethanol dispersion with a mass concentration of 0.2 g / mL and a sodium hydroxide solution with a mass fraction of 8% are mixed in a volume ratio of 1:2, and the mixture is swollen at room temperature for 3 to 4 hours and then vacuum filtered to obtain a solid powder. The obtained solid powder is dispersed in ethanol and stirred to be uniformly dispersed to obtain a dispersion with a mass fraction of 10%;
[0038] (2) TEOS, vinyl triethoxysilane and ethanol are mixed in a mass ratio of 3:1:100 and then charged into a three-necked flask. The dispersion is then added dropwise into the three-necked flask using a separatory funnel at a water bath temperature of 60 to 65° C. The dropping time is controlled to be 5 to 10 min. After stirring for 50 to 60 min, the mixture is allowed to stand for 30 to 40 min, and a solid filtrate is obtained by vacuum filtration. The solid filtrate is vacuum dried in a vacuum drying oven at a temperature of 80° C. for 6 to 8 h to obtain nanocomposite particles.
[0039] The present invention uses sodium hydroxide solution to swell the cellulose material to form a reaction layer on the cellulose surface, and then heats and dries the reaction layer to form gaps to form a reaction space, so that nano-SiO2 particles formed by hydrolysis of tetraethyl orthosilicate are combined with the cellulose material, and the steric hindrance of nano-cellulose prevents the aggregation and precipitation of nano-particles, thereby improving the synergistic effect. The present invention utilizes a large number of hydroxyl groups on cellulose molecules, each repeating unit contains 1 primary hydroxyl group and 2 secondary hydroxyl groups, but hydroxyl groups are very likely to form intramolecular hydrogen bonds and intermolecular hydrogen bonds, which limits the adsorption. Therefore, the present invention introduces nanofluids to open the bonds between hydroxyl groups, improve the adsorption activity of cellulose molecules, and add them into transformer oil. After the modification, the modified cellulose material has good adsorption performance, and a large number of polar groups exist on the molecule, which makes the molecule have extremely strong oleophobicity. Therefore, this feature can be used to adsorb free micro-water and impurities in the transformer oil, and the AC breakdown voltage is obviously affected by the free micro-water content. When the free micro-water content is high, the breakdown voltage value is relatively low. The addition of the composite nanoparticles of the present invention can adsorb and aggregate harmful inclusions and free micro-water in the transformer oil, further improving the insulation performance and positive impact breakdown performance of the modified transformer oil. After using for a period of time, the nano composite particles that adsorb and aggregate inclusions and micro-water are filtered and removed, and new nano composite particles are added again to achieve the self-purification effect of the transformer oil.
[0040] (3) the nanocomposite particles and a 30% by mass polyvinyl pyrrolidone ethanol solution were mixed and dispersed at a mass ratio of 1:100, and then transferred into a three-necked flask, and stirred at a speed of 300 r / min. During the stirring process, cerium nitrate in an amount of 20 to 25% by mass of the nanocomposite particles was added into the three-necked flask;
[0041] (4) After the addition of cerium nitrate is completed, the temperature is continued to be raised to 80-85° C. to react until the ethanol is completely evaporated, and the remaining product is placed in an oven and dried at 200° C. for 3-5 hours, and then wet-milled by a ball mill for 12 hours and passed through a 200-mesh sieve to obtain rare earth-doped nanoparticles;
[0042] The rare earth element doped in the rare earth doped nanoparticles of the present invention is easy to react with harmful impurities such as sulfur and oxygen in transformer oil to generate high melting point compounds, which can be adsorbed and gathered by the cellulose components of the nanoparticles themselves and discharged later, thereby reducing harmful inclusions in the oil and further improving the insulation performance of the modified transformer oil. The rare earth composite particles themselves have a high thermal conductivity. When they are evenly dispersed in the transformer oil, they can serve as a channel for heat conduction, improve the thermal conductivity of the transformer oil, and then improve its thermal conductivity.
[0043] In addition, the active groups or electrical properties on the surface of rare earth composite particles can be compounded with molecules in transformer oil by physical or chemical methods, thereby enhancing the interfacial compatibility between particles and oil molecules. This enhanced compatibility helps to reduce the agglomeration and precipitation of particles in oil, maintain their uniform dispersion in oil, and thus improve the insulation performance of modified transformer oil.
[0044] (5) The rare earth nanoparticles, acetic acid and ethanol were mixed in a mass ratio of 1:24:250 and dispersed evenly in an ultrasonic disperser, and then the obtained dispersion was refluxed at 70-75° C. for 2-3 hours, cooled to room temperature, and the precipitate was separated, washed with ethanol three times, and then dried at 70° C. for 2-3 hours to obtain surface-modified nanoparticles;
[0045] The present invention uses acetic acid to adsorb on the surface of nanoparticles in a bidentate chelate coordination mode, and the surface-modified nanoparticles greatly change the development form of streamers in transformer oil, inhibit the development speed of streamers, and improve the positive impact breakdown performance of transformer oil. The carbon chain structure of acetic acid is shorter than that of other carboxylic acids, so after the nanoparticles modified by acetic acid are added to transformer oil, more shallow traps are introduced, which will increase the migration rate of electrons in the nano oil, prompt the electrons generated by field ionization to quickly leave the positive ions, and make the electric field of the charge generated in the low-density area of the nano oil larger than that of pure oil, thereby weakening the electric field in the low-density area. In this way, the field intensity of the streamer head in the nano oil will be reduced, preventing the formation of a new discharge path, and then weakening the development speed of the streamer, so the acetic acid-modified nanoparticles have the best effect on improving the impact breakdown performance of transformer oil.
[0046] The good interfacial compatibility between the rare earth composite particles and transformer oil helps reduce interfacial thermal resistance, allowing heat to be transferred more smoothly in the oil. This helps improve the heat dissipation efficiency of the transformer, reduce its operating temperature, and thus extend its service life.
[0047] (6) According to the weight ratio, 20-30 parts of vegetable oil, 50-60 parts of mineral insulating oil, 3-8 parts of toluene diphenyl phosphate, 1-2 parts of stearic acid, 5-10 parts of surface-modified nanoparticles, and 0.5-0.7 parts of 2-methyl-benzotriazole are weighed, the vegetable oil is first vacuum filtered at room temperature, and then heated to 80-90° C., and then the mineral insulating oil is added, and the mixture is stirred and mixed at a speed of 80-100 r / min for 20-30 min, and then toluene diphenyl phosphate, stearic acid, and surface-modified nanoparticles are added, and ultrasonic oscillation treatment is performed at a power of 800-1000 W for 10-15 min. Finally, 2-methyl-benzotriazole is added and ultrasonic oscillation treatment is continued for 10-15 min to obtain self-purifying transformer oil.
[0048] Example 1
[0049] (1) A microcrystalline cellulose ethanol dispersion with a mass concentration of 0.2 g / mL and a sodium hydroxide solution with a mass fraction of 8% were mixed in a volume ratio of 1:2, and the mixture was swollen at room temperature for 3 hours and then vacuum filtered to obtain a solid powder. The obtained solid powder was dispersed in ethanol and stirred to disperse uniformly to obtain a dispersion with a mass fraction of 10%;
[0050] (2) TEOS, VTES and ethanol were mixed in a mass ratio of 3:1:100 and placed in a three-necked flask. The dispersion was then added dropwise to the three-necked flask using a separatory funnel at a water bath temperature of 60°C. The dropping time was controlled to be 5 min. After stirring for 50 min, the mixture was allowed to stand for 30 min and vacuum filtered to obtain a solid filtrate. The solid filtrate was vacuum dried in a vacuum drying oven at a temperature of 80°C for 6 to 8 h to obtain nanocomposite particles.
[0051] (3) the nanocomposite particles and 30% polyvinyl pyrrolidone ethanol solution were mixed and dispersed at a mass ratio of 1:100, and then transferred into a three-necked flask, and stirred at a speed of 300 r / min. During the stirring process, cerium nitrate in an amount of 20% of the mass of the nanocomposite particles was added into the three-necked flask;
[0052] (4) After the addition of cerium nitrate is completed, the temperature is continued to be raised to 80° C. to react until the ethanol is completely evaporated, and the remaining product is placed in an oven and dried at 200° C. for 3 h, and then wet-milled by a ball mill for 12 h and passed through a 200-mesh sieve to obtain rare earth-doped nanoparticles;
[0053] (5) The rare earth nanoparticles, acetic acid and ethanol were mixed in a mass ratio of 1:24:250 and dispersed evenly in an ultrasonic disperser, and then the obtained dispersion was refluxed at 70° C. for 2 h. After cooling to room temperature, the precipitate was separated, washed with ethanol three times, and then dried at 70° C. for 2 h to obtain surface-modified nanoparticles;
[0054] (6) According to the weight ratio, 20 parts of vegetable oil, 50 parts of mineral insulating oil, 3 parts of toluene diphenyl phosphate, 1 part of stearic acid, 5 parts of surface-modified nanoparticles, and 0.5 parts of 2-methyl-benzotriazole were weighed, and the vegetable oil was first vacuum filtered at room temperature, and then heated to 80° C., and then the mineral insulating oil was added, and the mixture was stirred and mixed at a speed of 80 r / min for 20 minutes, and then toluene diphenyl phosphate, stearic acid, and surface-modified nanoparticles were added, and ultrasonic oscillation treatment was performed at a power of 800 W for 10 minutes. Finally, 2-methyl-benzotriazole was added and ultrasonic oscillation treatment was continued for 10 minutes to obtain self-purifying transformer oil.
[0055] Example 2
[0056] (1) A microcrystalline cellulose ethanol dispersion with a mass concentration of 0.2 g / mL and a sodium hydroxide solution with a mass fraction of 8% were mixed in a volume ratio of 1:2, and the mixture was swollen at room temperature for 4 hours and then vacuum filtered to obtain a solid powder. The obtained solid powder was dispersed in ethanol and stirred to disperse uniformly to obtain a dispersion with a mass fraction of 10%;
[0057] (2) TEOS, VTES and ethanol were mixed in a mass ratio of 3:1:100 and placed in a three-necked flask. The dispersion was then added dropwise to the three-necked flask using a separatory funnel at a water bath temperature of 63°C. The dropping time was controlled to be 8 min. After stirring for 55 min, the mixture was allowed to stand for 35 min and vacuum filtered to obtain a solid filtrate. The solid filtrate was vacuum dried in a vacuum drying oven at 80°C for 7 h to obtain nanocomposite particles.
[0058] (3) the nanocomposite particles and 30% polyvinyl pyrrolidone ethanol solution were mixed and dispersed at a mass ratio of 1:100, and then transferred into a three-necked flask, and stirred at a speed of 300 r / min. During the stirring process, cerium nitrate in an amount of 23% by mass of the nanocomposite particles was added into the three-necked flask;
[0059] (4) After the addition of cerium nitrate is completed, the temperature is continued to be raised to 83° C. to react until the ethanol is completely evaporated, and the remaining product is placed in an oven and dried at 200° C. for 4 h, and then wet-milled by a ball mill for 12 h and passed through a 200-mesh sieve to obtain rare earth-doped nanoparticles;
[0060] (5) The rare earth nanoparticles, acetic acid and ethanol were mixed in a mass ratio of 1:24:250 and dispersed evenly in an ultrasonic disperser, and then the obtained dispersion was refluxed at 73° C. for 3 h. After cooling to room temperature, the precipitate was separated and washed with ethanol three times and then dried at 70° C. for 3 h to obtain surface-modified nanoparticles;
[0061] (6) According to weight, 25 parts of vegetable oil, 55 parts of mineral insulating oil, 5 parts of toluene diphenyl phosphate, 2 parts of stearic acid, 8 parts of surface-modified nanoparticles, and 0.6 parts of 2-methyl-benzotriazole were weighed, and the vegetable oil was first vacuum filtered at room temperature, and then heated to 85° C., and then the mineral insulating oil was added, and stirred and mixed at a speed of 90 r / min for 25 minutes, and then toluene diphenyl phosphate, stearic acid, and surface-modified nanoparticles were added, and ultrasonic oscillation treatment was performed at a power of 900 W for 13 minutes. Finally, 2-methyl-benzotriazole was added and ultrasonic oscillation treatment was continued for 13 minutes to obtain self-purifying transformer oil.
[0062] Example 3
[0063] (1) A microcrystalline cellulose ethanol dispersion with a mass concentration of 0.2 g / mL and a sodium hydroxide solution with a mass fraction of 8% were mixed in a volume ratio of 1:2, and the mixture was swollen at room temperature for 4 hours and then vacuum filtered to obtain a solid powder. The obtained solid powder was dispersed in ethanol and stirred to disperse uniformly to obtain a dispersion with a mass fraction of 10%;
[0064] (2) TEOS, vinyl triethoxysilane and ethanol were mixed in a mass ratio of 3:1:100 and placed in a three-necked flask. The dispersion was then added dropwise to the three-necked flask using a separatory funnel at a water bath temperature of 65°C. The dropping time was controlled to be 10 min. After stirring for 50 to 60 min, the mixture was allowed to stand for 40 min and vacuum filtered to obtain a solid filtrate. The solid filtrate was vacuum dried in a vacuum drying oven at a temperature of 80°C for 8 h to obtain nanocomposite particles.
[0065] (3) the nanocomposite particles and 30% polyvinyl pyrrolidone ethanol solution were mixed and dispersed at a mass ratio of 1:100, and then transferred into a three-necked flask, and stirred at a speed of 300 r / min. During the stirring process, cerium nitrate in an amount of 25% by mass of the nanocomposite particles was added into the three-necked flask;
[0066] (4) After the addition of cerium nitrate is completed, the temperature is continued to be raised to 80-85° C. to react until the ethanol is completely evaporated, and the remaining product is placed in an oven and dried at 200° C. for 5 h, and then wet-milled by a ball mill for 12 h and passed through a 200-mesh sieve to obtain rare earth-doped nanoparticles;
[0067] (5) The rare earth nanoparticles, acetic acid and ethanol were mixed in a mass ratio of 1:24:250 and dispersed evenly in an ultrasonic disperser, and then the obtained dispersion was refluxed at 75° C. for 3 h. After cooling to room temperature, the precipitate was separated, washed with ethanol three times, and then dried at 70° C. for 3 h to obtain surface-modified nanoparticles;
[0068] (6) 30 parts of vegetable oil, 60 parts of mineral insulating oil, 8 parts of toluene diphenyl phosphate, 2 parts of stearic acid, 10 parts of surface-modified nanoparticles, and 0.7 parts of 2-methyl-benzotriazole were weighed by weight. The vegetable oil was first vacuum filtered at room temperature, then heated to 90° C., and then the mineral insulating oil was added. The mixture was stirred and mixed at a speed of 100 r / min for 30 minutes. Then, toluene diphenyl phosphate, stearic acid, and surface-modified nanoparticles were added. The mixture was ultrasonically oscillated at a power of 1000 W for 15 minutes. Finally, 2-methyl-benzotriazole was added and ultrasonically oscillated for another 15 minutes to obtain self-purifying transformer oil.
[0069] Comparison Example
[0070] Comparative Example 1
[0071] The preparation method of this comparative example is substantially the same as that of Example 1, except that ordinary nano-silicon dioxide is used instead of the nano-composite particles of the present invention, and the other preparation steps remain unchanged to obtain transformer oil in the same manner;
[0072] Comparative Example 2
[0073] The preparation method of this comparative example is basically the same as that of Example 1, except that the rare earth-doped nanoparticles of the present invention are directly replaced by nanocomposite particles without being modified by doping with rare earth elements. The other preparation steps remain unchanged, and transformer oil is also obtained.
[0074] Comparative Example 3
[0075] The preparation method of this comparative example is basically the same as that of Example 1, except that rare earth-doped nanoparticles are directly used to replace the surface-modified nanoparticles of the present invention, and the surface-modified nanoparticles are not modified by doping with rare earth elements. The other preparation steps remain unchanged, and transformer oil is also obtained.
[0076] Comparative Example 4
[0077] The preparation method of this comparative example is basically the same as that of Example 1, except that oleic acid is used instead of the acetic acid of the present invention to modify the surface of the rare earth-doped nanoparticles, and the rare earth element is not doped thereto. The other preparation steps remain unchanged, and transformer oil is also prepared.
[0078] Comparative Example 5
[0079] The preparation method of this comparative example is basically the same as that of Example 1, except that the surface-modified nanoparticles are not added, and the other preparation steps remain unchanged to obtain transformer oil in the same manner;
[0080] The performance of Examples 1-3 and Comparative Examples 1-3 of the present invention were tested respectively, and the test results are shown in Table 1:
[0081] Detection method:
[0082] The properties of the prepared transformer oil and the transformer oil used for 6 months were tested respectively;
[0083] Table 1 Performance test results
[0084]
[0085]
[0086] It can be seen from the test data in the above table that the transformer oils prepared in Examples 1-3 of the present invention have significantly improved performance data compared to the pure transformer oil in Comparative Example 5, which can confirm that the technical solution of the present application is highly feasible;
[0087] Next, the performance of the control example 1 and the embodiment 1 of the present invention is compared. Since ordinary nano-silicon dioxide is used in the control example 1 instead of the nano-composite particles of the present invention, the other preparation steps remain unchanged and the transformer oil is also prepared; however, the insulation and impact breakdown properties of the transformer oil are reduced, and the various properties after six months of use are also significantly reduced. This proves that the present invention swells the cellulose material with a sodium hydroxide solution to form a reaction layer on the cellulose surface, and then creates gaps on the reaction layer by heating and drying to form a reaction space, so that the nano-SiO2 particles formed by the hydrolysis of tetraethyl orthosilicate are combined with the cellulose material, and the steric hindrance of the nano-cellulose is used to prevent the agglomeration and precipitation of the nano-particles, thereby improving the synergistic effect. The present invention utilizes a large number of hydroxyl groups on the cellulose molecules, each repeating unit contains 1 primary hydroxyl group and 2 secondary hydroxyl groups, but the hydroxyl groups are very easy to form molecular bonds. Internal hydrogen bonds and intermolecular hydrogen bonds limit the adsorption. Therefore, the present invention opens the bonds between hydroxyl groups and improves the adsorption activity of cellulose molecules by introducing nanofluids. After adding the nanofluids to transformer oil, the modified cellulose material has good adsorption performance. The presence of a large number of polar groups on the molecules makes the molecules have extremely strong oleophobicity. Therefore, this feature can be used to adsorb free micro-water and impurities in the transformer oil. The AC breakdown voltage is obviously affected by the free micro-water content. When the free micro-water content is high, the breakdown voltage value is relatively low. The addition of the composite nanoparticles of the present invention can adsorb and aggregate harmful inclusions and free micro-water in the transformer oil, further improving the insulation performance and positive impact breakdown performance of the modified transformer oil. After using for a period of time, the nano-composite particles that adsorb and aggregate inclusions and micro-water are filtered and removed, and new nano-composite particles are added again to achieve the self-purification effect of the transformer oil.
[0088] Next, the comparative document 2 is compared with the embodiment 1 of the present invention. Since the comparative example 2 directly uses nanocomposite particles to replace the rare earth doped nanoparticles of the present invention, and does not modify the rare earth elements, the other preparation steps remain unchanged, and the transformer oil is also obtained; resulting in a decrease in the thermal conductivity and insulation of the final transformer oil. It can be confirmed that the rare earth elements doped in the rare earth doped nanoparticles of the present invention are easy to react with harmful impurities such as sulfur and oxygen in the transformer oil to generate high melting point compounds, which can be adsorbed and aggregated by their own cellulose components and discharged later, thereby reducing harmful inclusions in the oil and further improving the insulation performance of the modified transformer oil. The rare earth composite particles themselves have a high thermal conductivity. When they are evenly dispersed in the transformer oil, they can serve as a channel for heat conduction, improve the thermal conductivity of the transformer oil, and then improve its thermal conductivity.
[0089] In addition, the active groups or electrical properties on the surface of rare earth composite particles can be compounded with molecules in transformer oil by physical or chemical methods, thereby enhancing the interfacial compatibility between particles and oil molecules. This enhanced compatibility helps to reduce the agglomeration and precipitation of particles in oil, maintain their uniform dispersion in oil, and thus improve the insulation performance of modified transformer oil.
[0090] Finally, the control examples 3 and 4 were compared with the embodiment 1. Since the control example 3 directly used the rare earth-doped nanoparticles instead of the surface modified nanoparticles of the present invention, the rare earth elements were not doped and modified, and the other preparation steps were unchanged, the transformer oil was also prepared; the control example 4 used oleic acid instead of the acetic acid of the present invention to modify the surface of the rare earth-doped nanoparticles, and the rare earth elements were not doped and modified, and the other preparation steps were unchanged, and the transformer oil was also prepared; the thermal conductivity, insulation and impact breakdown resistance of the control examples 3 and 4 were all decreased, and the decrease in the control example 4 was greater than that in the control example 3, thus It can be confirmed that the present invention is adsorbed on the surface of nanoparticles in a bidentate chelating coordination mode by acetic acid, the surface modified nanoparticles greatly change the development form of streamers in transformer oil, suppress the development speed of streamers, and improve the positive impact breakdown performance of transformer oil. The carbon chain structure of acetic acid is shorter than other carboxylic acids, so after the nanoparticles modified by it are added to transformer oil, more shallow traps are introduced, which will increase the migration rate of electrons in the nano oil, prompt the electrons generated by field ionization to leave the positive ions quickly, so that the electric field of the charge generated in the low-density area of the nano oil is increased compared with pure oil, thereby weakening the electric field in the low-density area. In this way, the field intensity of the streamer head in the nano oil will be reduced, preventing the formation of a new discharge path, and then weakening the development speed of the streamer, so the acetic acid modified nanoparticles have the best effect on the impact breakdown performance improvement of transformer oil.
[0091] The good interfacial compatibility between the rare earth composite particles and transformer oil helps reduce interfacial thermal resistance, allowing heat to be transferred more smoothly in the oil. This helps improve the heat dissipation efficiency of the transformer, reduce its operating temperature, and thus extend its service life.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the technical principles of the present invention, and these improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A self-purifying transformer oil, characterized in that: The following raw materials are included by weight: 20-30 parts vegetable oil; 50-60 parts of mineral insulating oil; 3-8 parts of toluene diphenyl phosphate; 1-2 parts of stearic acid; 5-10 parts of nanocomposite particles; 0.5-0.7 parts of 2-methyl-benzotriazole; The raw materials for preparing the nano composite particles include microcrystalline cellulose, ethanol, sodium hydroxide, ethyl orthosilicate and vinyl triethoxysilane.
2. The self-purifying transformer oil according to claim 1, characterized in that: The nanocomposite particles are also modified to become rare earth doped nanoparticles; The modified raw materials of the rare earth doped nanoparticles include nano composite particles, polyvinyl pyrrolidone, cerium nitrate and ethanol.
3. The self-purifying transformer oil according to claim 1, characterized in that: The rare earth doped nanoparticles are also surface modified to become surface modified nanoparticles; The modification raw materials of the surface-modified nanoparticles include rare earth nanoparticles, acetic acid and ethanol.
4. A method for preparing a self-purifying transformer oil as claimed in claim 3, characterized in that: The specific preparation steps are: (1) By weight, 20 to 30 parts of vegetable oil, 50 to 60 parts of mineral insulating oil, 3 to 8 parts of toluene diphenyl phosphate, 1 to 2 parts of stearic acid, 5 to 10 parts of surface-modified nanoparticles, and 0.5 to 0.7 parts of 2-methyl-benzotriazole are weighed; (2) first vacuum filter the vegetable oil at room temperature, then heat it to 80-90° C., then add mineral insulating oil, stir and mix at a speed of 80-100 r / min for 20-30 min, then add toluene diphenyl phosphate, stearic acid, and surface-modified nanoparticles, and treat with ultrasonic oscillation at a power of 800-1000 W for 10-15 min; (3) Finally, 2-methyl-benzotriazole is added and the ultrasonic oscillation treatment is continued for 10-15 minutes to obtain self-purifying transformer oil.
5. The method for preparing a self-purifying transformer oil according to claim 4, characterized in that: The preparation method of the surface modified nanoparticles is: Rare earth nanoparticles, acetic acid and ethanol are mixed in a mass ratio of 1:24:250 and put into an ultrasonic disperser for uniform dispersion. The dispersion is then refluxed at 70-75°C for 2-3 hours. After cooling to room temperature, the precipitate is separated, washed three times with ethanol, and then dried at 70°C for 2-3 hours to obtain surface-modified nanoparticles.
6. The method for preparing a self-purifying transformer oil according to claim 5, characterized in that: The preparation method of the rare earth nanoparticles is: (1) mixing and dispersing the nanocomposite particles and a 30% by mass polyvinyl pyrrolidone ethanol solution at a mass ratio of 1:100, transferring the mixture into a three-necked flask, stirring the mixture at a speed of 300 r / min, and adding cerium nitrate in an amount of 20 to 25% by mass of the nanocomposite particles into the three-necked flask during the stirring process; (2) After the addition of cerium nitrate is completed, the temperature is continued to rise to 80-85° C. to react until the ethanol is completely evaporated, and the remaining product is placed in an oven and dried at 200° C. for 3-5 hours. The product is then wet-milled in a ball mill for 12 hours and passed through a 200-mesh sieve to obtain rare earth-doped nanoparticles.
7. The method for preparing a self-purifying transformer oil according to claim 6, characterized in that: The preparation method of the nanocomposite particles is as follows: (1) A microcrystalline cellulose ethanol dispersion with a mass concentration of 0.2 g / mL and a sodium hydroxide solution with a mass fraction of 8% are mixed in a volume ratio of 1:2, and the mixture is swollen at room temperature for 3 to 4 hours and then vacuum filtered to obtain a solid powder. The obtained solid powder is dispersed in ethanol and stirred to be uniformly dispersed to obtain a dispersion with a mass fraction of 10%; (2) Ethyl orthosilicate, vinyl triethoxysilane and ethanol are mixed in a mass ratio of 3:1:100 and loaded into a three-necked flask. The dispersion is then added dropwise into the three-necked flask using a separatory funnel at a water bath temperature of 60 to 65°C. The dropping time is controlled to be 5 to 10 min. After stirring for 50 to 60 min, the mixture is allowed to stand for 30 to 40 min, and a solid filtrate is obtained by vacuum filtration. The solid filtrate is vacuum dried in a vacuum drying oven at 80°C for 6 to 8 h to obtain nanocomposite particles.